Multi-Functional Reconfigurable Intelligent Surface Assisted Security Communication Systems Under Imperfect CSI of Eavesdroppers - Rui-Bao Zhang; Dian-Wu Yue; Yu Sun (IEEE Access)
In order to overcome the “multiplicative fading” loss and half-space coverage limitations faced by reconfigurable intelligent surfaces (RIS) in secure communications, a more practical multi-functional reconfigurable intelligent surface (MF-RIS) with coupled phase shifts is introduced to assist in enhancing the security performance of multiple-input single-output (MISO) systems. In addition, the paper especially focuses on the case where the eavesdropper’s channel state information (CSI) is imperfect. Based on the bounded CSI error model, this paper strictly limits the upper bound of information leakage to potential eavesdroppers and seeks to maximize the system sum rate by jointly optimizing the beamforming at the transmitter side and the coupled phase shifts of the MF-RIS. For this nonconvex optimization problem, we combine the penalty dual decomposition method, weighted minimum mean square error (WMMSE) method, S-Procedure Lemma, and general sign-definiteness to design an efficient solution. Simulation results show that: 1) All MF-RIS schemes achieve better secrecy performance gains than other existing RIS designs; and 2) Compared to the optimal independent phase shifts, coupled phase shifts of MF-RIS only lead to a slight performance loss.